The 5G race: is Colombia lagging behind in implementation and information security? - Bornachera Zarate, Leydy Stefany; Vargas González, Iván David; Ardila Sánchez, Ismael Antonio (Ingeniería Solidaria, 2023)
Introduction: This article focuses on analyzing “The 5G Race: Is Colombia Lagging Behind in Implementation and Information Security?”, through a literature review developed at the Universidad Distrital in 2023.Problem: Despite successful pilot schemes, Colombia has not achieved large-scale 5G deployments like other nations. The following problematic question arises: How is Colombia faring in implementing successful 5G cases compared to other countries in terms of regulatory and information security aspects?Objective: To compile up-to-date literature on the progress of 5G worldwide and contrast it with Colombia, to determine regulatory, pilot and security challenges.Methodology: A search was conducted in academic and government databases such as Scopus, Web of Science, IEEE Xplore, SpringerLink, ScienceDirect and Google Scholar, focusing on identifying reports, case studies and articles on the current state of 5G worldwide and in Colombia. The keywords used in the search were: “5G”, “5G regulation”, “5G information security”, “Colombia”, “availability” among other related words.Results: The comparative analysis allows us to identify gaps and challenges in Colombia for a comprehensive implementation of 5G.Conclusion: The review suggests that Colombia is lagging behind in the adoption of 5G. Regulatory, infrastructure investment, and cybersecurity challenges remain.Originality: This article provides an up-to-date comparative analysis between the state of adoption of 5G technology globally and in Colombia.Limitations: Focuses on success stories and regulatory, safety and pilot aspects.
Keywords: 5G; regulation; information security; Colombia; availability